ICT-Based Instructional Material Development: A Study of Communication Department Students - Prasetiyo, M. Teguh (IJET (Indonesian Journal of English Teaching), 2017)
Technology as an essential matter has been integrated in today’s education for the sake of innovative and cutting-edge medium for English language teaching (ELT). Also, the students’ demands in learning English should be accommodated since they are in relation to the specialized study or the professional required of the students. This paper attempted to explain how the process of ICT-based instructional materials for undergraduate students of Communication Department is developed. This research occupies Richards (2001) model of R and D. There were three groups participated to this research. The students (N 50), lecturer (N 1) and the curriculum coordinator (N 1), from those three participants, were achieved by triangulation with respect to data collection sources. The finding shows that most of the respondents agree to use ICT-based instructional material in their learning process. It means ICT-based instructional material is proper to be implemented since the practicality and ease of usage. The feedback from the students indicates that they like the appearance of the instructional material and it attracts the students to use it to support their learning.